The implementation of the role play technique in speaking class of second semester at STKIP PGRI Banjarmasin 2015 - Fathul Zannah; Maya Nanda Riyanti (Lentera: Jurnal Ilmiah Kependidikan, 2016)
Speaking is the one of basic skills that facilitating learners to master English. Speaking skill focuses on the students’ ability in producing English for daily communication as natural as in their own mother tongue. Many techniques can be applied in teaching speaking, one of them is role play technique. Some researches stated that role play technique can improve students’ speaking ability, but some researches stated the opposite. Thus, this presents study is intended to investigate what is not appropriate when the role play is applied in speaking class, to know the way the lecturer implements the role play technique and the problems faced by students on the role play technique. To know the result of this study, the researcher used quantitative research as the design. The population of this study was all students of English Department at STKIP PGRI Banjarmasin and the sample of this study was 44 students of second semester and one speaking lecturer who taught speaking II. The instruments used in this study were observation and questionnaire. The result of this study showed that the way the lecturer implemented the role play technique in speaking 2 was in line with the explanation from Huang. They were decide on the teaching materials, select situations and create dialogs, have students modify the situations and the dialogue and the last evaluate and check students’ comprehension. The researcher also found the students’ problems when the role play technique was implemented in speaking 2. They were the students found difficulties in developing their creativity, they found difficulties when they were asked to create a situation for role play, they felt their repertory of vocabulary are less, they found difficulties when they were asked to make a dialog for role play, they prefer to choose their own roles for role play, they felt scared, nervous or shy when they are asked to perform their role play in front of the class.